Subject: care for a terminally ill child - Kowacka, Ewa (Journal of Education, Health and Sport, 2019)
A terminal illness of a child is a traumatic experience for both the child and the family. The illness destroys their current life, The terminally ill patient experiences total pain, which includes not only physical pain caused by lesions, but also psychological, social and spiritual one. The terminal disease of a child is an exceptional experience also for medical staff, for whom it cannot be an ordinary medical case. The terminally ill patient requires an HPC environment, in which the death perspective is inscribed. The whole environment of a terminally ill child, both family and medical staff, should follow the rules of thanatopedagogy, a discipline whose subject is education for good dying, or with respect for the subjectivity and dignity of a person facing death. HPC, regardless of whether it is performed in home, hospital or hospice settings, it must be closely correlated with support for the closest family of a terminally ill child, especially parents and siblings. Only then it can be an effective support group for the child, a factor raising the quality of life in dying, which is the main goal of HPC.